Perbandingan Metode Dempster-Shafer dan Certainty Factor Untuk Mendiagnosa Jenis Gangguan Bipolar Berbasis Website (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Bipolar is a mental illness that have very drastic emotional transformation. Bipolar disorders can interfere sufferer's activity if it has not been detected early. In general, the bipolar disorders sufferers difficult to control their circumstances or moods and it requires the proper treatment of the expert. An expert system to diagnose the kind of bipolar disorders built on this study using comparative methods of Depmster-Shafer and certainty factor based on website. The main expectation of this expert system application is to make it easier for the expert to diagnose bipolar disorders as well as to speed up the consultation process. In addition, this study aims to compare the two methods to determine the best method. The accuracy of this study is 93% of the certainty factor method while for the Dempster-Shafer method is 80% which can be summarized that certainty factor method is better than Dempster-Shafer in diagnose bipolar disorders because it has a higher degree of accuracy.